2019
DOI: 10.1016/j.conbuildmat.2019.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the curing type on the mechanical properties of lightweight concrete with polypropylene and steel fibres

Abstract: This study assessed the effect of steel and polypropylene fibres at various volume contents on concrete incorporating lightweight expanded clay aggregate (LECA) and water/binder (W/B) ratios of 0.37 and 0.42. The concrete specimens were cured under six curing conditions: wet, 3-day wet, 14-day wet, air-dry controlled, air-dry uncontrolled, and 90 °C vapour. The use of lightweight aggregates in the construction industry has drawn the attention of researchers and, on the other hand, fibres with a high strain-har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(18 citation statements)
references
References 54 publications
1
16
1
Order By: Relevance
“…The SD values under dry curing regime were averagely about 18.9% more than those under wet curing regime. Meanwhile, the SD values of mixes made with PF were averagely obtained 23.2% more than those with no PF, which can be attributed to the generated airvoids in mixes by the inclusion of PF as reported by Madandoust et al [29]. The SD values of concrete mixes increased up to 44.4% and 85.5% by 50% and 100% replacements of coarse natural aggregate with RCA, respectively.…”
Section: Schmidt Rebound Hammer Testsupporting
confidence: 58%
See 2 more Smart Citations
“…The SD values under dry curing regime were averagely about 18.9% more than those under wet curing regime. Meanwhile, the SD values of mixes made with PF were averagely obtained 23.2% more than those with no PF, which can be attributed to the generated airvoids in mixes by the inclusion of PF as reported by Madandoust et al [29]. The SD values of concrete mixes increased up to 44.4% and 85.5% by 50% and 100% replacements of coarse natural aggregate with RCA, respectively.…”
Section: Schmidt Rebound Hammer Testsupporting
confidence: 58%
“…The saturated surface-dry condition was introduced in all aggregates to avoid absorbing the free water, particularly by RCA. Concerning the optimum amount of PF content, Madandoust et al [29] showed that the highest amount of compressive strength was obtained for the concrete with 0.1% PF.…”
Section: Proportioning and Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…11-13. Therefore, by considering the fact that concrete can be classified as a brittle material with low flexural strength [44][45][46][47][48][49][50][51][52][53], the concrete crushing was followed by the effective participation of GFRP bars in carrying the generated stress intensity, particularly in the pure bending zone. For instance, at the nominal moment, the maximum tensile stress in G12-N was depicted in the tension zone near to the mid-span, where the maximum tensile stress in GFRP bars was found to be 213.…”
Section: Failure Mode and Stress Distribution Of Frp Reinforced Concrete Specimensmentioning
confidence: 99%
“…Due to the primary characteristics of LWC (i.e., adequate compressive strength, acceptable durability, low density and improved properties of thermal conductivity) its applications in structural applications allow the use of smaller size foundations and beam and column cross-sections. Likewise, the use of LWC in place of conventional concrete reduces the structural dead load, which leads to a reduction in seismic forces [8,9]. Structural LWC also benefits from energy savings, as it possesses improved thermal conductivity [10][11][12] and sound insulation properties [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%